Incidence of post tuberculosis chronic obstructive pulmonary disease in a tertiary centre in Malaysia - Ban, Andrea Yu-Lin; Mohamed Faisal Abdul Hamid,; Chong, GY; Syed Zulkifli Syed Zakaria, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2020)
Pulmonary tuberculosis (PTB) and chronic obstructive pulmonary disease (COPD) are important causes of mortality and morbidity in Malaysia. The number of tuberculosis (TB) cases in Malaysia appears to be increasing and there were 500,000 Malaysians diagnosed with COPD in 2016. A substantial number of PTB patients go on to develop post tubular airway disease. Past infection with TB has been shown to contribute to the aetiology of COPD. We conducted a one year cross-sectional study in outpatient setting involving adult subjects in Universiti Kebangsaan Malaysia Medical Centre (UKMMC) with a history of pulmonary tuberculosis three years prior to the study. We excluded subjects with bronchial asthma, COPD, interstitial lung disease and bronchiectasis. Airflow obstruction was defined as FEV1 : FVC ratio <0.70. The COPD Assessment Test (CAT) questionnaire was used. Eighty-two subjects were recruited with a median age of 52.5 years (IQR 36-62). Male predominance (56.1%) with 29 (35.4%) smokers. Eighteen (22%) subjects had airflow obstruction. Six (33%) out of these subjects were smokers. Fourteen(17%) had restrictive pattern and 50 (61%) had normal spirometry results. Five subjects (22.22%) had mild obstruction, 7 (44.44%) moderate obstruction, and 6 (33.33%) had severe obstruction. There was a positive correlation between chest X-ray abnormalities and age with airflow obstruction (P<0.05). Abnormal spirometry pattern was found in 39% of subjects. Post TB-COPD incidence was 22% in those who completed TB treatment. There appeared to be an association between abnormal chest radiograph findings with airflow obstruction in subjects with history of PTB.